If it's not what You are looking for type in the equation solver your own equation and let us solve it.
14=15x-(2x+12)
We simplify the equation to the form, which is simple to understand
14=15x-(2x+12)
Remove unnecessary parentheses
14=15x-2x-12
We move all terms containing x to the left and all other terms to the right.
-15x+2x=-12-14
We simplify left and right side of the equation.
-13x=-26
We divide both sides of the equation by -13 to get x.
x=2
| 9x+5x+2+6=10x+4+3x | | 1(5x+8)2=375 | | 9(x-3)+6(x-1)=2x | | abs(7x-4)=abs(4x-8) | | x^3+8x-4=0 | | a^2*x^3-1/8*a^2*(1+x)^3 | | 0.5+7y=-25 | | 4(x-1)-(5-2x)=5 | | 6(x-3)+1=10 | | 2(X-10)=70 | | C=A(150c) | | 3(5x+8)=375 | | a^2x^3-1/8a^2*(1+x)^3 | | x^3+8x+2=0 | | 9(w+3)=5w-13 | | y=1.23x+0.19x^2 | | 6x=4(5-x) | | 7(1-4b)=231 | | 7x^2+2sqrt(14)x+2=0 | | 4x+5x-9=2 | | 7-8(-6+8k)=119 | | 2x(3x-1)=5x+1 | | -5(5-8r)+4r=-113 | | 15x-2x+7=9+15-4x | | 4(x-3)=7 | | -3(4-4a)+a=92 | | 5x^2-5x=14 | | 4(-6+8v)=-120 | | F(4)=2 | | F(4)=y | | 4(6+8v)=-120 | | t+3/4=7/8 |